The Role Of Village Funds For Community Welfare In A Review Of Maqasid Sharia, Talang Emppat District, Central Bengkulu Regency - CINTYA, Nanda Tri (Integration: Journal Of Social Sciences And Culture, 2023)
Purpose:This study aims to examine the role of village funds in community welfare in Bengkulu Province. Methodology:The type of research conducted in this research is descriptive qualitative research with a phenomenological approach. Primary data in this study were data obtained directly from selected informants through direct interviews with the Head of Kembang Seri Village, Pulau Panggung Village and Taba Pasmah Village, Secretary of Kembang Seri Village, Tengah Padang Village and Padang Ulak Tanjung Village, Kembang Seri Village Community, Tengah Padang Village and Padang Ulak Tanjung Village. Secondary data in this study is obtained from the website and written data from informants. This secondary data is used as complementary and supporting data from the primary data. Secondary data in this study relate to the phenomenon to be studied. Findings:The results of this study indicate that the planning process for using Village Funds in the Village follows maqashid sharia, especially in all dharuriyat aspects. Implication:Based on the results of research and discussion, it can be concluded that the planning process for using village funds in the Village is in accordance with maqasid sharia. However, several programs still need to try to bring mashlahah to the village community to practice.